The Relationship of Vitamin D 25(OH)D Levels with The Incidence of Hypertension on The Elderly at Public Health Clinic - Ikram S. Akbar; Irfan K. Pratama; Achmad Zaki; Sayyid Ridho; Dede Moeswir; Muniroh Muniroh (The Avicenna Medical Journal, 2020)
Introduction: Hypertension is a chronic disease which its presence is often not known until occurrence of other diseases. Several studies had previously investigated the relationship between vitamin D concentration and hypertension. However, no concluding result is obtained. This paper aimed to determine the relationship between vitamin D 25(OH)D concentration and hypertension onelderly at a public health clinic located at Reni Jaya, South Tangerang.Methods: This was cross-sectional study conducted in a public health clinic between January 2017 to January 2018. One hundred and fifty subjects were recruited by consecutive sampling after informed consent were obtained.Anamnesis, physical examination, and anthropometric measurement were performed by general practitioners. The following day serum vitamin D 25(OH)D examination were collected and examined at certied laboratory. The data werethen analyzed using Chi-Square test.Results : As many as 80 (53.4%) subjects had insufficient vitamin D 25(OH)D concentration (25-50 nmol/L). Stage I and II hypertension were found in 51 (34.0%) and 34 (22.7%) subjects, respectively. Age was significantly associated with hypertension (p=0.048). No significant association was observed between vitamin D 25 (OH)D and hypertension p=0.347.Conclusions: There was no significant association between serum vitamin D 25(OH)D and hypertension.